Kota Utama Menurut Ibn Rūsyd - Siti Yakutil Amnah (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2017)
This article focuses on Ibn Rūsyd’s thoughtson “Excellent City” (al-madīnah al-fāḍilah) in his book, Plato’s Republic. Ibn Rūsyd was commenting Plato’s book, Republic. He made Republic as a means to against the government in his era.Ibn Rūsyd’s thought on excellent city addresses specifically his thoughts on the following ideas, such as meaning, aim, characteristics, virtues and the government of excellent city. Word “city” in this article refers to state or city-state.